Distributed precoder design for inter-cell interference suppressing in multi-cell MU-MIMO systems - Desheng Wang; Yifan Yang; Guangxi Zhu; Xiaojiang Du (2013 IEEE Wireless Communications and Networking Conference (WCNC), 2013)
In this paper, we propose a distributed precoder design algorithm for suppressing the inter-cell interference(ICI) and maximizing the average throughput of a multi-cell multiuser multi-input multi-output(MU-MIMO) system. Motivated by the recent results of the distributed signal-to-leakage-plus-noise ratio(SLNR) model for ICI coordination(ICIC), we design a joint optimization algorithm to achieve the pareto-optimal average system throughput. Existed SLNR-based algorithms only consider downlink optimization problem of one optimized factor, which will bring a restriction to the further improvement of the system performance. In our proposed algorithm, the SLNR-based downlink precoder and the transmitting power factor will be designed from a joint optimization problem, and the closed-form pareto-optimal solutions of both optimized factors can be obtained through matrix analysis and decomposition techniques. Simulation results show that the proposed distributed joint precoder design algorithm can significantly increase the average cell throughput and improve the resource efficiency while effectively reducing the system overhead.